Hospital admissions for hypertensive crisis in the emergency departments: a large multicenter Italian study. - Giuliano Pinna; Claudio Pascale; Paolo Fornengo; Sebastiana Arras; Carmela Piras; Pietro Panzarasa; Gianpaolo Carmosino; Orietta Franza; Vincenzo Semeraro; Salvatore Lenti; Susanna Pietrelli; Sergio Panzone; et al. (PLoS ONE, 2014)
Epidemiological data on the impact of hypertensive crises (emergencies and urgencies) on referral to the Emergency Departments (EDs) are lacking, in spite of the evidence that they may be life-threatening conditions. We performed a multicenter study to identify all patients aged 18 years and over who were admitted to 10 Italian EDs during 2009 for hypertensive crises (systolic blood pressure ≥220 mmHg and/or diastolic blood pressure ≥120 mmHg). We classified patients as affected by either hypertensive emergencies or hypertensive urgencies depending on the presence or the absence of progressive target organ damage, respectively. Logistic regression analysis was then performed to assess variables independently associated with hypertensive emergencies with respect to hypertensive urgencies. Of 333,407 patients admitted to the EDs over the one-year period, 1,546 had hypertensive crises (4.6/1,000, 95% CI 4.4-4.9), and 23% of them had unknown hypertension. Hypertensive emergencies (n = 391, 25.3% of hypertensive crises) were acute pulmonary edema (30.9%), stroke (22.0%,), myocardial infarction (17.9%), acute aortic dissection (7.9%), acute renal failure (5.9%) and hypertensive encephalopathy (4.9%). Men had higher frequency than women of unknown hypertension (27.9% vs 18.5%, p<0.001). Even among known hypertensive patients, a larger proportion of men than women reported not taking anti-hypertensive drug (12.6% among men and 9.4% among women (p<0.001). Compared to women of similar age, men had higher likelihood of having hypertensive emergencies than urgencies (OR = 1.34, 95% CI 1.06-1.70), independently of presenting symptoms, creatinine, smoking habit and known hypertension. This study shows that hypertensive crises involved almost 5 out of 1,000 patients-year admitted to EDs. Sex differences in frequencies of unknown hypertension, compliance to treatment and risk of hypertensive emergencies might have implications for public health programs.